As wide as the world is wise : reinventing philosophical anthropology - Jackson, Michael (Columbia University Press, 2016)
"Philosophy and anthropology have long debated questions of difference: rationality versus irrationality, abstraction versus concreteness, modern versus premodern. What if these disciplines instead focused on the commonalities of human experience? Would this effort bring philosophers and anthropologists closer together? Would it lead to greater insights across historical and cultural divides? In As Wide as the World Is Wise, Michael Jackson encourages philosophers and anthropologists to mine the space between localized and globalized perspectives, to resolve empirically the distinctions between the one and the many and between specific forms of life and life itself. His project balances remote, epistemological practice with immanent reflection, promoting a more situated, embodied, and sensuous approach to the world and its in-between spaces. Drawing on a lifetime of ethnographic fieldwork in West Africa and Aboriginal Australia, Jackson resets the language and logic of academic thought from the standpoint of other lifeworlds. He extends Kant's cosmopolitan ideal to include all human societies, achieving a radical break with elite ideas of the subjective and a more expansive conception of truth."--Jacket
Keywords: Philosophical anthropology; Anthropology : Philosophy; filosofinen antropologia; filosofia; antropologia; filosofisk antropologi; filosofi; antropologi